2008
DOI: 10.1007/s00417-008-0866-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for visual outcome after intravitreal bevacizumab for macular edema due to branch retinal vein occlusion

Abstract: Preoperative presence of macular ischemia can be useful in predicting the outcome of visual acuity after intravitreal bevacizumab for macular edema due to BRVO. The early gainers who favorably responded to the initial intravitreal bevacizumab injection are most likely to benefit from the bevacizumab treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 24 publications
5
61
0
1
Order By: Relevance
“…They are also useful to reduce ischemic progression and to manage complications, such as neovascular glaucoma [61]. There are some prognostic factors for better outcome, such as better initial VA, no foveal hemorrhages, no macular ischemia, detection of VA gain after first injection, young age and final central retinal thickness [45,48,62,63]. But there are limits in efficacy, need for multiple injections, rebound effect of macular edema and nonresponders.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also useful to reduce ischemic progression and to manage complications, such as neovascular glaucoma [61]. There are some prognostic factors for better outcome, such as better initial VA, no foveal hemorrhages, no macular ischemia, detection of VA gain after first injection, young age and final central retinal thickness [45,48,62,63]. But there are limits in efficacy, need for multiple injections, rebound effect of macular edema and nonresponders.…”
Section: Treatmentmentioning
confidence: 99%
“…The dosage varies between 1 and 2.5 mg, there are no different outcomes [39,40,41,42,43,44,45,46,47,48]. The Pan-American Collaborative Retina Study group concluded that intravitreal injections of bevacizumab at doses up to 2.5 mg were more effective in improving VA and reducing macular edema at 6 months (compared to 1.25 mg), but the study had no control group [44].…”
Section: Treatmentmentioning
confidence: 99%
“…10,13,28 poor visual outcome correlates with increased foveal avascular zone (FaZ) 29 or disruption of perifoveal capillaries seen in fluorescein angiograms. [30][31][32] Similarly in BRvO patients treated with grid laser, those with intact perifoveal capillaries have a better visual prognosis than those with perifoveal capillary disruption. 31 Nonperfusion is a significant baseline factor for development of disc or retinal neovascularization in patients with BRvO with the highest risk at ≥5.5 disc areas.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…Most of the investigations have employed the administration of bevacizumab for the treatment of ME [98,99,100,101,102,103,104,105]. In particular, it has been demonstrated that its intravitreal administration brings about a reduction in VEGF levels that occurs in parallel with a decrease in the central retinal thickness and improvement in VA of patients affected by BRVO [102].…”
Section: Treatmentmentioning
confidence: 99%
“…Two prospective case series revealed that a VA improvement similar or even better than that achievable by grid laser photocoagulation can be maintained up to 1 year of follow-up through repeated injections [103, 104]. Important prognostic factors for the functional outcome are the existence of macular ischemia and the detection of an initial gain in VA after the first bevacizumab injection [105]. …”
Section: Treatmentmentioning
confidence: 99%